Condição periodontal, perda dentária e diferenças socioeconômicas em adultos e idosos brasileiros - Prado, Rosana Leal do [UNESP] (2015)
The aim of this study was to verify the correlations of periodontal disease, tooth loss and edentulousness with socioeconomic and demographic factors, health needs and health services as well as the impact of these correlations on oral health among Brazilian adults and elderly and compare the standard estimate of need with a sociodental assessment. The data originated from a national epidemiological survey on oral health conducted in 2010 by the Brazilian Health Ministry (SBBrasil 2010). The sample comprised 9779 people between 35-44 years old and 7619 elderly between 65-74 years old. The oral health outcomes were as follows: bleeding on probing and/or dental calculus, periodontal loss of attachment, tooth loss and edentulousness. Education level and declared income were used as indicators of socioeconomic status. Gender, ethnicity, region of residence, use of dental care, impact of teeth in daily activities, and other variables were added to the models to adjust the regression analysis. Poisson regression was performed to verify the socioeconomic and demographic disparities in oral health with regard to the proximal and distal determinants of health available in the data set. McNemar's test was applied to compare standard estimates of need and the respective impact-related. The results showed associations (p<0.05) between socioeconomic and demographic aspects and all oral health variables. People who had up to 8 years of formal education had increased the prevalence to develop any of the oral diseases on this study. As much as adults whom declared income up to 500 BRL, that had increased the prevalence to develop three of the four studied conditions. Ethnicity had association with bleeding on probing/or dental calculus (PR=1.19) and tooth loss (PR=1.45) between adults who declared themselves as brown. Having a consultation...